2019
DOI: 10.1039/c8sc05066j
|View full text |Cite
|
Sign up to set email alerts
|

Frontier molecular orbital effects control the hole-catalyzed racemization of atropisomeric biaryls

Abstract: Biaryl atropisomerization is dramatically accelerated by the removal of an electron. The planar transition state is preferentially stabilized from depopulation of the highest occupied molecular orbital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 35 publications
0
27
2
Order By: Relevance
“…The energy barrier for the rotation of one arm was studied by conformational search (Figure S31, detailed method was summarized in SI), which was calculated as 72.44 kJ·mol –1 . It is higher than the rotational energy of C—C in freely rotating n ‐butane (19 kJ·mol –1 ), but lower than that of conformationally stabilized 1,1'‐bi‐2‐naphthol (167 kJ·mol –1 ) . Compared to the reported longer version of tetratopic tpy‐porphyrin ligand, our design introduced more restriction to the rotation of tpy with a short arm, and constructed more compact structures with higher stability …”
Section: Resultsmentioning
confidence: 91%
“…The energy barrier for the rotation of one arm was studied by conformational search (Figure S31, detailed method was summarized in SI), which was calculated as 72.44 kJ·mol –1 . It is higher than the rotational energy of C—C in freely rotating n ‐butane (19 kJ·mol –1 ), but lower than that of conformationally stabilized 1,1'‐bi‐2‐naphthol (167 kJ·mol –1 ) . Compared to the reported longer version of tetratopic tpy‐porphyrin ligand, our design introduced more restriction to the rotation of tpy with a short arm, and constructed more compact structures with higher stability …”
Section: Resultsmentioning
confidence: 91%
“…[34][35][36] The greater racemization of 3 a may indicate that this intermediate is longer-lived for this substrate, allowing more time for racemization to occur. The formation of radical intermediates may also account for the loss of ee, as has been noted by Pappo [37] and further investigated by Paton [38] for BINOL atropisomers. DFT studies indicate that single electron transfer to 2 (forming 2 * À ) causes a reduction in rotational barrier of 15-20 kcal mol À 1 , sufficient to enable significant racemization (see ESI for further discussion).…”
mentioning
confidence: 74%
“…[55] Ta na nd Paton have shown that the hole-catalysedr acemization of atropisomericb iaryls occurs throughatwo-step mechanism in aprocess controlled by frontier molecular orbitals. [56] 2.6.5 Mechanism not known…”
Section: Rotationa Bout Single Bondsmentioning
confidence: 99%